Experimental, Numerical, and Analytical Studies of Uniaxial Compressive Behavior of Concrete Confined by Ultra-High-Performance Concrete - Shijun Wang; Chun Liu; Yunfei Tian; Xing Wang; Teng Tong; Saiyang Zhuo (Advances in Civil Engineering)
This research examines the uniaxial behavior of core concrete, which is confined by a UHPC (ultra-high-performance concrete) shell, through experimental, numerical, and analytical methods. Various configurations, including different UHPC shell shapes, thicknesses, and core concrete compressive strengths, were tested until failure occurred. Results indicate that the UHPC shell altered the failure modes and enhanced the maximum stress and corresponding strain in uniaxial loading. Additionally, in square and rectangular specimens, debonding between the UHPC and NC (normal concrete) interfaces was observed. Furthermore, we constructed numerical models which integrate the concrete damage plasticity model for NC/UHPC and the coupled adhesive-frictional model implemented in cohesive elements. The model accurately reflects the crack and debonding evolution of the tested specimen. Subsequently, an analytical stress-strain model for uniaxial loading was created based on the experimental results. The confining pressure for square/rectangular specimens was determined using Airy’s function. The validity of the analytical model was verified by comparing its predictions with the experimental results.